PEMBERDAYAAN MASYARAKAT DALAM MENGIMPLEMENTASIKAN NILAI PANCASILA UNTUK MENGHADAPI GLOBALISASI DAN ERA INDUSTRI 4.0 - Wicipto Setiadi; Iwan Joesoef Erar; Muhammad Helmi Fahrozi (GoAcademica Research dan Publishing, 2020)
The impact of technology is very fast, in principle it can be a threat to Indonesian citizens, especially in some areas such as the capital lifting regions. This should be anticipated starting from the youth / I, to prevent the erosion of the values ​​of Pancasila, which is no longer disseminated on a massive scale by the government. Therefore, community service activities to promote the values ​​of Pancasila become important for legal academics so that every citizen continues to prioritize the values ​​of Pancasila in their daily lives. Community Empowerment and Outreach is carried out in Bekasi City, as a capital for the capital city which is the target of industrialization for technological development, so the need to face the threat of decreasing the understanding of state ideology and the state foundation becomes appropriate to be carried out in Bekasi City, the Community Service Team forms a community and several programs that sustainable so that in the life of the nation and state in the city of Bekasi, especially in North Bekasi Sub-district, Bahagia Sub-district, residents of the Bahagia Komlek and Barokah Complex RT 0 7 RW 07, can understand and continue to understand the values ​​of Pancasila as the ideology of the state and the basis of the state.